Analisis Capaian Pembangunan SDM dan Faktor-faktor Pendorong Penyerapan Tenaga Kerja di Provinsi Bali - Theresia Mutiara Galistya (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
Human resource development in the Bali Province can be illustrated through the development of the Human Development Index (HDI) achievements and employment conditions. Until 2018, HDI of Bali Province recorded continued to grow and is at a